2013
DOI: 10.1017/s1047951113000176
|View full text |Cite
|
Sign up to set email alerts
|

Double right coronary artery and its clinical implications

Abstract: Congenital anomalies of the coronary arteries are present in 0.2-1.4% of the general population. These anomalies represent one of the most confusing issues in the field of cardiology and challenges for interventional cardiologists and cardiac surgeons if the anomalies are unrecognised. Double right coronary artery is one of the rarest coronary arteries. Previously, the probability of developing atherosclerotic changes in patients with a double right coronary artery was considered to be equal to that in those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(97 reference statements)
1
18
0
Order By: Relevance
“…We reported a case of double RCA from a single ostium in a 68-year-old male as an incidental finding in CAG. In previous studies, it has been reported to be predominant in male patients (9)(10)(11). In our case, the CAG findings besides the coronary anomaly were normal; thus, it is possible that the patient's dyspnea was due to the underlying chronic obstructive pulmonary disease and cor pulmonale.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…We reported a case of double RCA from a single ostium in a 68-year-old male as an incidental finding in CAG. In previous studies, it has been reported to be predominant in male patients (9)(10)(11). In our case, the CAG findings besides the coronary anomaly were normal; thus, it is possible that the patient's dyspnea was due to the underlying chronic obstructive pulmonary disease and cor pulmonale.…”
Section: Discussionsupporting
confidence: 45%
“…Patients with double RCA have a high prevalence of atherosclerotic coronary artery disease (CAD). These patients have an increased risk of unsuspected complications of atherosclerotic CAD (10,11). These patients can also show a positive stress test while having no significant stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[9] [12] Patients with double right coronary artery are asymptomatic until an accidentally discovered during coronary angiography. [9][13] [14] This anomalous coronary artery poses a risk for earlier development of coronary atherosclerotic disease so the acute coronary syndrome is possible because of duplication of the artery, therefore the clinical presentations are the inferior myocardial infarction or anterior myocardial infarction. [9][13] [14] In addition, there are difficulties of this anomaly for the angiographer at the time of the catheterization with a challenge for the radiologist in interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…[9][13] [14] This anomalous coronary artery poses a risk for earlier development of coronary atherosclerotic disease so the acute coronary syndrome is possible because of duplication of the artery, therefore the clinical presentations are the inferior myocardial infarction or anterior myocardial infarction. [9][13] [14] In addition, there are difficulties of this anomaly for the angiographer at the time of the catheterization with a challenge for the radiologist in interpretation. [15] [16] The coronary intervention or cardiac operation is more complicated in individuals with a double right coronary artery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation